Impact/outcome measures for libraries - Poll, Roswitha (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
Libraries today document their performance for the most part only in data of input and output (e.g. size of the collection, number of issues, of reference answers etc.). If they do more, they evaluate the quality and user-orientation of their services by applying performance indicators or user satisfaction surveys. Data of high use or high user satisfaction seem to indicate that users benefit from the library’s services. But in demonstrating the library’s value to the financing authorities or the public it would be much more effective if libraries could show a direct impact/outcome of their services on their users. Such outcome might be either a monetary value attributed to one case of use, or the impact on the users’ skills and knowledge, their information literacy. Quite a number of projects in different countries have tested methods to catch this ’outcome’. They have tried • to assess the value assigned by the population to certain library services, • to find a connection between success in studies or research and library use, • to assess the library’s impact on students’ information literacy, • to explore the information behaviour of groups in order to specify the library’s role in information research and information delivery. The paper describes the different starting points for assessing outcome of library services.